Studi Komparatif Ekuitas Merek Produk Buatan Malaysia dan Indonesia - Listiana, Erna (Fakultas Ekonomi dan Bisnis, UNTAN, 2015)
The purpose of this study is to assess and obtain empirical evidence by testing different responsetowards brand equity products made in Indonesia and Malaysia. The observed product isprocessed food products biscuit, considering the existence of this Malaysia